2011
DOI: 10.1002/chem.201101170
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide‐Doped Multicolor GdF3 Nanocrystals for Time‐Resolved Photoluminescent Biodetection

Abstract: Lanthanide lights: Water‐soluble lanthanides (Ln3+)‐doped GdF3 nanocrystals synthesized through a facile one‐step route can be used as time‐resolved photoluminescence biolabels to detect trace amounts of biomolecules (avidin of 74 pM) and robust MRI positive‐contrast agents. Multicolor emissions, spanning a wide spectral region, can be achieved in Ln3+‐doped GdF3 nanocrystals under single‐wavelength excitation by finely tuning the combinations of Ln3+ dopants and their concentrations (see figure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 89 publications
2
78
0
2
Order By: Relevance
“…[1][2][3][4] To date, many efforts have been dedicated to fabricating GdF 3 nanoparticles with various sizes and morphologies. [1][2][3][4] To date, many efforts have been dedicated to fabricating GdF 3 nanoparticles with various sizes and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] To date, many efforts have been dedicated to fabricating GdF 3 nanoparticles with various sizes and morphologies. [1][2][3][4] To date, many efforts have been dedicated to fabricating GdF 3 nanoparticles with various sizes and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…The decay time of the green and red emission bands depends on the concentrations of the Yb and Er in the phosphor and a more detailed analysis is underway. In time gated fluorescence based biomaging, 43 longer decay time is a favorable factor to discriminate the noises arising from scattered light and autofluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…8a) [26]. It was observed that the steady-state PL spectrum for the mixture of GdF 3 : Dy 3+ and RBITC was dominated by the emission of RBITC upon excitation at 272 nm, whereas only the Dy 3+ emission from the NPs was detected in the TRPL spectrum with a delay time of 50 μs and a gate time …”
Section: Time-resolved Luminescent Bioassaymentioning
confidence: 99%
“…Therefore, they are emerging as promising next-generation luminescent nano-bioprobes for versatile biomedical applications. Particularly, the long-lived downshifting luminescence (DSL) and high photochemical stability of Ln 3+ -doped NPs make them ideal alternative to Ln 3+ -chelates for TRPL biodetection to eliminate the short-lived background noise from scattered lights and autofluorescence from the biological samples [26,27]. Such unwanted background noise can also be overcome by using the unique anti-Stokes upconverting luminescence (UCL) and persistent luminescence of Ln This review summarizes the most recent advances in the development of inorganic lanthanide nano-bioprobes and their salient applications for background-free luminescent bioassays.…”
mentioning
confidence: 99%